A Little Princess - Burnett's, Frances Hodgson; Nang Chan Yeema (New York, USA Grosset & Dunlap Publisher, Inc., 1996)
Sara Crew has wonderful toys, pretty dresses, and even a pony! Then suddenly, everything changes. Sara has to wear rags, live in an attic, and work for a mean old woman. What will happen to Sarah?
Keywords: Story Collection